Das kognitive Gefühl von Präsenz in medialen Tutorien oder Ist reale Präsenzlehre präsenter als virtuelle Präsenzlehre? - Kirsten Oleimeulen (IUBH Internationale Hochschule, 2019)
– On the basis of an increasing demand for distance learning courses, combined with a steady educational demand for digitization in schools and colleges, it seems time to strive for a proof of quality combined with a quality improvement of medial tutorials. Almost without exception, previous research in media reception research is based on the "two-level model of presence experience" by Wirth et al (2007). Presence is considered here as a perception illusion of non-existent media, which arises multifactorial. Influenced by unconscious attention and spatial cues, a Spatial Situation Model (SSM) arises in the user, which competes with the inner picture of the current spatial situation. Depending on which spatial model receives acceptance, the student locates his egocentric frame of reference in tutorial or real space. The perceptual hypothesis is continually being retested. In this model, involvement, suspension of belief, attention, and user traits play a mediating role. Presence experience is a dichotomous variable. It only knows the two states "felt being present" and "not feeling present". Based on this definition of presence and the associated model, a research concept is constructed using the classical methodological, psychological approach that combines traditional methods of psychophysiology with new techniques of eye-tracking. This article does not claim to be exhaustive, but is intended as a rough outline and exploration of the proposed research approach to provide a basis for decision-making and discussion.
Keywords: I19; 650; Medienrezeptionsforschung; perceptual illusion of non mediation; soziale Präsenz; Hypothesentheorie der Wahrnehmung; Präsenzerleben auf 2 Ebenen; spatial cues; Involvement; Aufmerksamkeit; Suspension of belief